Using Discourse Markers to Enhance Students’ Speaking Skills - Suryadi Suryadi; Asep Muhyidin; Syafrizal Syafrizal (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
English proficiency is a desirable performance quality. The aim of this study is to determine the effectiveness of discourse markers in improving English speaking skills. This study employs a quantitative methodology. This study employed a pre-test-posttest group design, The study's demographic and sample consist of Class XI IPA 80 students from the academic year 2023/2024. The researcher employed the snowball sampling method to ascertain the requisite sample size. Prior to conducting the pre and post tests, the researcher assessed the instrument's validity and reliability using SPSS. This was done by examining the scores on the corrected item total correlation, which measures the correlation between item scores and the total item score. The students were designated as Group A (experimental) and Group B (control). Subsequently, students engage in a Pretest to ascertain any disparities among them. The researcher provided discourse markers to both groups; however, only the experimental group employed them, whilst the control group did not. The experimental group will receive treatment including the use of discourse markers. The T test was employed as the data analysis tool. The results indicated that the observed T value was 7.313, and the Sig. value was less than 0.05. Therefore, it can be inferred that the utilisation of discourse markers enables students to enhance their proficiency in English speaking. This research is significant as it can enhance English language acquisition, particularly by highlighting the significance of teachers' role in teaching discourse markers during English language learning.